2019
DOI: 10.1002/jctb.6255
|View full text |Cite
|
Sign up to set email alerts
|

The biological mechanisms of butanol tolerance and the application of solvent‐tolerant bacteria for environmental protection

Abstract: Toxicity caused by the accumulation of butanol in fermentation media is an important factor limiting the concentration of butanol. There is currently no systematic research in place investigating the butanol tolerance mechanism of bacteria such as Clostridium acetobutylicum, which adapts to butanol stress and regulates its growth and metabolism. Here, research results related to the butanol tolerance of C. acetobutylicum are reviewed to understand the molecular basis of changes in butanol‐tolerant strains. Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…As mentioned above, acetoin and hexanoic acid were produced by every Listeria in similar quantities, however, butanol was produced in very different amounts by every isolate, for instance, the amount determined in ST-8/CT-8813 and ST-87/CT-4557 was quadruple the amount produced by ST-3/CT-8722. The production of butanol by bacteria has been most recently and extensively explored due to its potential uses as an alternative biofuel to ethanol [24, 25]. Clostridium strains have been intensively employed for the production of butanol; however, it is limited by the effects of product cytotoxicity to microorganisms that catalyse its production, and therefore less than 13 g l −1 of butanol is produced during batch fermentation [26].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, acetoin and hexanoic acid were produced by every Listeria in similar quantities, however, butanol was produced in very different amounts by every isolate, for instance, the amount determined in ST-8/CT-8813 and ST-87/CT-4557 was quadruple the amount produced by ST-3/CT-8722. The production of butanol by bacteria has been most recently and extensively explored due to its potential uses as an alternative biofuel to ethanol [24, 25]. Clostridium strains have been intensively employed for the production of butanol; however, it is limited by the effects of product cytotoxicity to microorganisms that catalyse its production, and therefore less than 13 g l −1 of butanol is produced during batch fermentation [26].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, such solvent tolerance has a range of potential applications in bioremediation (e.g. Gao et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This obvious unprofitability of the process is due to the severe toxicity of butanol to bacteria [ 5 , 6 ]. The effects of butanol on microbial cells include the destruction of the phospholipid bilayer and the membrane lipopolysaccharides [ 7 ], inhibition of the cell membrane ATPase activity, and the glucose absorption [ 8 ]. This is why several genetic approaches have been applied to enhance microbial resistance to butanol; that is, chemical mutagenesis [ 9 , 10 , 11 ], genomic libraries construction and screening [ 12 , 13 ], forced genomic evolution [ 14 , 15 ], and genome shuffling [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analysis has shown that groEL overexpression increases the butanol resistance of Escherichia coli , Bacillus subtilis , Lactococcus lactis , and Lacticaseibacillus paracasei NFBC 338 [ 20 , 21 ]. Transcriptomic methods have also revealed the importance for butanol tolerance of efflux pump components, such as those encoded by acrA and acrB in E. coli [ 16 ] or srpB in Pseudomonas putida [ 22 ], the two-component system encoded by btrTM [ 23 ], the master regulator Spo0A in C. acetobutylicum [ 8 ], and the nrps3 biosynthetic cluster in C. saccharoperbutylacetonicum N1–4 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%